Exploring the Distribution of Zn2+ in Inner and Outer Helmholtz Planes of the Electrical Double Layer of Soil based on Wien Effect. Issue 1 (27th December 2018) - Wang, Yu-Jun; Fan, Ting-Ting; Cui, Pei-Xin; Alves, Marcelo Eduardo; Li, Cheng-Bao; Zhou, Dong-Mei; Friedman, Shmulik P.; Sparks, Donald L.
Abstract : Core Ideas: Wien effect measurements assess adsorbed cations distribution over the Helmholtz planes of the electrical double layer. Assessing cation distributions in the electrical double layer improves bioavailability predictions for plant nutrients and pollutant metals. Most of the zinc adsorption takes place in the inner Helmholtz plane layer and occurs via chemical interactions. The classical electrical double layer (EDL) theory explains the interaction between ions and charged soil colloidal particles, playing an importance role in the bioavailability and toxicity of ions in soils, which are of agricultural and environmental concern. A new approach based on extrapolating measurements of suspension Wien effect is suggested to determine the adsorbed ions distribution in the different compartments of the EDL. The new approach was applied to assess Zn 2+ distribution in the EDL of Zn‐saturated soil colloids. The results showed that more than 84% of Zn 2+ was adsorbed via chemical interactions and located in the inner Helmholtz plane layer. The remaining Zn 2+ fraction was electrically adsorbed and distributed in the outer Helmholtz plane layer (0.3 to 2.1%) and in the Gouy–Chapman diffuse layer (7.4 to 15.0%). Independently, the results of linear combination fitting of extended x‐ray absorption fine structure (EXAFS) spectra indicated that the contents of outer‐sphere Zn in one paddy soil and the boggy soil were consistent with the proportions of Zn 2+ electrostatically interacting with the soil colloids based on the extrapolation of the suspension Wien effect method, while the contents of outer‐sphere Zn in a second paddy soil, the yellow cinnamon soil, and the yellow brown soil was overestimated by the EXAFS method. The approach proposed in this paper to assess specific and electrostatic adsorption deepens our understanding of metal sorption processes in soils and reinforces the adequacy of the Grahame–Stern–Gouy–Chapman model of the EDL to describe the ion distribution in the solid‐water interface.